2017
DOI: 10.1007/s00261-017-1389-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitating whole lesion tumor biology in rectal cancer MRI: taking a lesson from FDG-PET tumor metrics

Abstract: The novel tumor metrics TLD and TLP revealed similar results to established metrics for correlation with tumor response with equivalent or superior inter-reader agreements and we recommend that these be studied in larger trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Furthermore, PET/MRI permits the assessment of cellular density with diffusion-weighted imaging (DWI). In studies of MRI alone, quantitative metrics such as the apparent diffusion coefficient (ADC) have been used to track response to treatment or predict clinical outcomes (6,7). The repeatability of ADC metrics for integrated PET/MRI systems is unknown and might be different from MRI-only systems.…”
mentioning
confidence: 99%
“…Furthermore, PET/MRI permits the assessment of cellular density with diffusion-weighted imaging (DWI). In studies of MRI alone, quantitative metrics such as the apparent diffusion coefficient (ADC) have been used to track response to treatment or predict clinical outcomes (6,7). The repeatability of ADC metrics for integrated PET/MRI systems is unknown and might be different from MRI-only systems.…”
mentioning
confidence: 99%
“…78 In another study, the authors evaluated tumor volume based on DWI (defining total lesion diffusion as the total DWI tumor volume multiplied by mean volumetric ADC), demonstrating that tumor volume based on DWI was correlated with pathological tumor regression and was comparable to DWI-and DCE-based volumetry. 79 Pooled analysis demonstrated the superiority of DWI over T2WI volumetry, wherein volumetric DWI measurements after neoadjuvant therapy were able to predict pCR with a sensitivity and an overall accuracy of 65% and 90%, respectively. 80 Functional Imaging DWI may provide functional information on the microstructure of the tumor environment through the assessment of differences in water proton mobility.…”
Section: Tumor Volumetrymentioning
confidence: 91%
“…One study demonstrated that tumor volume on T2WI and its reduction correlated with the ypT stage, although MRI overestimated the volume of residual tumor 78 . In another study, the authors evaluated tumor volume based on DWI (defining total lesion diffusion as the total DWI tumor volume multiplied by mean volumetric ADC), demonstrating that tumor volume based on DWI was correlated with pathological tumor regression and was comparable to DWI‐ and DCE‐based volumetry 79 …”
Section: Research Directions On Response Assessmentmentioning
confidence: 99%
“…T2-weighted signal intensity-selected volumetry of post-CRT MRI performed better than visual qualitative T2 volumetry in predicting pCR in patients with LARC[151]. Posttreatment total lesion diffusion (TLD = total DWI tumor volume x mean volumetric ADC) was better correlated than the total DWI tumor volume with histopathological tumor responses after CRT in patients with LARC[152].…”
Section: Quantitative Image Analysis Methodsmentioning
confidence: 99%